If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x+4x+3x-13x-6x=6
We move all terms to the left:
15x+4x+3x-13x-6x-(6)=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2
| 10-4b=4-3b | | x+.08x=28.61 | | 6+8p=11+7p | | 25c+10c2=0. | | -13+1+6n-5n=8n-n | | 51+4x-3=90 | | -v+1-3-5=v+3 | | -19=-3x+2*1 | | 63x=-9 | | 11u−9u=18 | | 11+3n=n+3 | | 5^2n-37=100 | | 4+7a=7a+1+a | | 10s-6s=8 | | 4+7a=7a | | 11g-7g=20 | | -4(2+x)=-5 | | 4(x-10)=-20 | | 28x+x^2=1040 | | 50+2x-19=90 | | -7-3p+3p=2p-3p | | 3x+5=-x-19 | | -4(2+x=-5 | | 26=x+21 | | 3(-5x+5)=3x-21 | | -4(x-7)=-32 | | 0.75(8x+4)=7x+2 | | 10(x+5)=-40 | | 2b-7=7-4b+5b-13 | | -8x+7(-3x-3)=-46-4x | | -3(x+6)=-11 | | -6x+8+2x=12 |